DETERMINANTS AND COMPARISON OF BANK STABILITY OF COMMERCIAL BANKS AND COOPERATIVE BANKS: EMPIRICAL EVIDENCE FROM AMERICAN - WANG, YIAN (2020)
This dissertation is focused on bank stability of commercial banking and cooperative banking in America. The main purpose is to analyze whether different factors have different effects on the bank stability of commercial banks and cooperative banks and which banks are more stable. For previous studies, most of them concentrate on commercial banks but hardly compared it with other types of banks. Based on their research, the author evaluates bank stability by Z-score. The author briefly introduces the history and background of the American banking system. After that, the author runs an empirical analysis to measure the relationship between the factors and the Z-score. The process is divided into three parts. First, it analyzes the macro variables and Z-score. Second, it measures the bank-level factors and Z-score. Finally, it runs a regression model for all variables and Z-score. According to the results, it can be concluded that cooperative banks are more stable than commercial banks. The results also show macro variables like GDP growth rate, exchange rate and unemployment rate are significant with bank stability. For bank-level variables, liquidity ratio and bank size are negative with commercial banks, which are also negatively with cooperative banks. The difference is the cost-income ratio is obvious with cooperation while it is not significant in commercial banks.